Pengaruh Tenaga Kerja dan Pertumbuhan Penduduk Terhadap Pertumbuhan Ekonomi di Indonesia Tahun 2017–2022 - I Gusti Made Yoga Swastika (Warmadewa Economic Development Journal (WEDJ), 2024)
This research was conducted to fill the gap in previous research results regarding differences of opinion regarding Labor and Population Growth on Economic Growth. This research focuses on the unemployed population as an indicator of labor and population growth on economic growth in Indonesia. The aim of this research is to determine the influence of Labor on Economic Growth and Population Growth on Economic Growth in Indonesia for 6 years, namely from 2017 - 2022. The research method used in this research is panel data regression by taking data on labor, population growth and growth economy in a period of 6 years, namely from 2017 – 2022 from the internet. The results of this research using panel data regression analysis and hypothesis testing (t test and R2 determination test) show that the labor variable (X1) is stated to have a negative and insignificant effect on economic growth (Y) in 2017 - 2022, the population growth variable (X2) states that it has a significant and negative influence on economic growth (Y) in 2017 – 2022.